2022
DOI: 10.3390/microorganisms10010101
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Adsorption and Biodegradation of Trichloroethylene on Biochar from Pine Wood Wastes: A Combined Approach for a Sustainable Bioremediation Strategy

Abstract: Towards chlorinated solvents, the effectiveness of the remediation strategy can be improved by combining a biological approach (e.g., anaerobic reductive dechlorination) with chemical/physical treatments (e.g., adsorption). A coupled adsorption and biodegradation (CAB) process for trichloroethylene (TCE) removal is proposed in a biofilm–biochar reactor (BBR) to assess whether biochar from pine wood (PWB) can support a dechlorinating biofilm by combining the TCE (100 µM) adsorption. The BBR operated for eight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Recently, commercial polyhydroxy butyrate combined with pine biochar improved the bioreductive dechlorination of TCE (approximately 80 mg/day) from aqueous solutions in a new reactor setup and small pilot scale ( Rossi et al, 2022a ). In a subsequent study, they confirmed that biofilm-biochar reactor was able to remove more than 99% of 100 μM TCE, and that Dehalococcoides mccartyi and tceA , bvcA , and vcrA genes played significant roles in TCE biodegradation ( Rossi et al, 2022b ). Furthermore, the addition of biochar supported nanoscale iron sulfide composite (CMC-FeS@biochar) followed by Corynebacterium variabile HRJ4 achieved 99% of TCE (10 mg/L) removal, and acetylene was the main product of the chemical process, whereas ethylene was the main product of the biological process ( Lyu et al, 2018 ).…”
Section: Material-mediated Enhanced Biodegradationmentioning
confidence: 88%
See 3 more Smart Citations
“…Recently, commercial polyhydroxy butyrate combined with pine biochar improved the bioreductive dechlorination of TCE (approximately 80 mg/day) from aqueous solutions in a new reactor setup and small pilot scale ( Rossi et al, 2022a ). In a subsequent study, they confirmed that biofilm-biochar reactor was able to remove more than 99% of 100 μM TCE, and that Dehalococcoides mccartyi and tceA , bvcA , and vcrA genes played significant roles in TCE biodegradation ( Rossi et al, 2022b ). Furthermore, the addition of biochar supported nanoscale iron sulfide composite (CMC-FeS@biochar) followed by Corynebacterium variabile HRJ4 achieved 99% of TCE (10 mg/L) removal, and acetylene was the main product of the chemical process, whereas ethylene was the main product of the biological process ( Lyu et al, 2018 ).…”
Section: Material-mediated Enhanced Biodegradationmentioning
confidence: 88%
“…Biochar-microorganism collaboration can promote the biodegradation of TCE (Figure 5C; Liu et al, 2021;Rossi et al, 2022b). The advantages include: (1) the adsorption of TCE on biochar can create a low-toxic environment for microorganisms;…”
Section: Biochar-microorganismmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve a maximum adsorption condition, far superior to any soil, the carbonaceous reference sorbent material pine wood biochar (PWB, Plößberg bei Tirschenreuth, Germany) was selected. Previous studies have shown that this material has a high adsorption capacity due to its high organic carbon content and remarkable surface development, making it an alternative to activated carbon [48,49]. A series of isothermal batch experiments with PWB/contaminant/surfactant were conducted at room temperature (23 ± 2 • C) and pressure in 20 mL batch reactors (VWR International glass vials, Milan, Italy), using different amounts of sorbent material (10, 20, 50, 80, 100, and 200 mg), and 50 mg L -1 of contaminant solution.…”
Section: Batch Configurationmentioning
confidence: 99%